Right Testicular Artery Occlusion and Acute Appendicitis by Angiostrongylus costaricensis - Luis Enrique Sánchez-Sierra; Roberto Antonio Martínez-Quiroz; Héctor S. Antúnez; Humberto Cabrera-Interiano; Fernando Josué Barrientos-Melara (Case Reports in Surgery)
Introduction. Angiostrongylus costaricensis is a nematode from the superfamily Metastrongyloidea, whose etymology is “roundworm that lives in blood vessels”. This parasite can be found from the southern United States to northern Argentina and southern Brazil. In 1983, Morera and Ruiz published the first case of a testicular artery occlusion by A. costaricensis. Case Presentation. A five year old boy presented with eight days of pain, denying trauma backgrounds and followed with an increase of volume. The treatment was a right simply orchiectomy, finding necrosis of the testicle, the biopsy showed reddish-purple aspect and soft consistency. Histologic studies reveled the presence of a worm inside the testicular artery. Conclusion. The diagnosis of A. costaricensis infection should be considered in all pediatric patients, with signs and symptoms of orchitis or acute abdomen, from endemic areas, may cause occlusion of the testicular artery and appendicular artery causing testicular and cecal appendix necrosis, respectively, even putting the patient’s life at risk. The diagnosis is complex, because the clinical manifestations are similar to an orchitis or acute abdomen, therefore, the definitive diagnosis is made during the surgical intervention and histopathological study.